Liberalisasi Pengadaan Barang dan Jasa: Konflik Kepentingan Negara Maju Versus Negara Berkembang (Lex Jurnalica, 2007)
Liberalization ofÂ government procurement has become a major issue in Doha Round. Basically, developed countries try to insert Government procurement as multilateral agreement and developing countries should apply international trade principle in government procurement. Those are transparency and non discrimination principles. Legal consequence of non discrimi-nation principle leads to no different treatment between foreign and domestic bidder. This effect considerably endanger national interest all developing countries and this issue has no binding forces. Due to that fact, finally WTO established a Working Group on Transparency in Government procurement as initial step in liberalizing government procurement which supported by several international organizations.Keywords:Â Trade Liberalization, Government Procurement and Conflict of Interest Between Developed and Developing Countries.